2021
DOI: 10.1177/01600176211023879
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the City-transport System of Urban Agglomeration through Improved Space Syntax Analysis

Abstract: From the perspective of city-transport system, this article applies space syntax to analyze the physical integration of cities. Traditionally, space syntax is mainly applied to urban areas, buildings, and other scales. However, when space syntax is applied to the configuration analysis of urban agglomeration, the change of scale causes changes in spatial perception and human behavioral patterns. Thus, we present a new method of space syntax. This method defines the lane and track between entrance and exit, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Previous studies in this field have shown that the distribution of cities has obvious traffic directionality, and the evolution of the traffic network is closely related to the development of the cities. The higher the level of cities, the greater the density of their traffic network [30], and the traffic network causes changes to the scale structure and interactions of cities [31,32]. Lanzhou and Xining, as the political and economic cores of the region, have high town levels, large regional advantages, and close transportation with surrounding regions.…”
Section: Plos Onementioning
confidence: 99%
“…Previous studies in this field have shown that the distribution of cities has obvious traffic directionality, and the evolution of the traffic network is closely related to the development of the cities. The higher the level of cities, the greater the density of their traffic network [30], and the traffic network causes changes to the scale structure and interactions of cities [31,32]. Lanzhou and Xining, as the political and economic cores of the region, have high town levels, large regional advantages, and close transportation with surrounding regions.…”
Section: Plos Onementioning
confidence: 99%
“…The road integration degree of traffic data represented the accessibility of regional traffic and measured the potential of one space to attract traffic to that location (Figure 9). The road traffic complexity was represented by counting the length of all line segments within the 1 km radius and calculating the total length of the line segments within the range [10]. The space syntax results showed that the Yangchunhu areas of Wuhan Qingshan and the Wangjiawan (Zhongjiacun) areas of Wuhan Hanyang were hotspots of traffic crime with high road integration degrees.…”
Section: The Impact Of the Object Environment On Traffic Crimementioning
confidence: 99%
“…Spatial syntax is a method used to study the relationship between spatial organisation and human society through the quantitative description of spatial structures that contain landscapes, buildings and urban systems [19][20][21]. Spatial syntax emphasises that the relationship between spaces is important, as an essentially mathematical approach based on graph theory [22,23].…”
Section: Literature Reviewmentioning
confidence: 99%